Genetic Relationship among Bananas in AA, AAB and BB Groups Using Random Amplified Polymorphic DNA (RAPD) and Sequence Related Amplified Polymorphism (SRAP) Techniques - Sujitra Phothipan,; Benchamas Silayoi,; Kawit Wanichkul,; Somsak Apisitwanich, (Agriculture and Natural Resources, 2005)
RAPD and SRAP techniques were introduced to analyse the genetic relationship among 29 accessions of banana in AA, AAB and BB groups at Department of Genetics and Department of Horticulture, Kasetsart University, Thailand. The genetic similarity and UPGMA were determined. The results showed that the SRAP technique was very similar to the RAPD technique for detecting genetic polymorphism and genetic relationship. The phylogenetic tree of RAPD and SRAP data showed two main clusters, AA-AAB and BB banana genome accessions. The BB group consisted of two subgroups with 8 cultivars. Within this group, Kluai Pa from Nakhon Si Thammarat and Kluai Pa from Na Khom, Kluai Tani Eisan and Kluai Tani Dam showed very close relationships. In the AA-AAB, it consisted of 21 cultivars. It was divided into three subgroups. First subgroup consisted of 6 from 10 AAB bananas. These cultivars were placed close to Kluai Pa Phrae. The second subgroup consisted of 4 AAB bananas, Kluai Klai, Kluai Nga Chang, Kluai Khom and Kluai Nom Sao, and all AA bananas except only ‘Kluai Pa Abisiania’ which was in the forth subgroup. The cultivar Kluai Klai and Kluai Nga Chang (AAB) were more closely related to Kluai Flava and Kluai Pa Pli Som while Kluai Khom and Kluai Nom Sao were closer to acuminata cultivars than the others.